Development of Fatigue Models for Asphalt Layers - Aguiar Moya, José Pablo (2025)
With the emergence of new, more sophisticated mechanistic-empirical pavement design guides at the international level, we are compelled to study them and, where feasible, consider their implementation. However, are these guides truly applicable to Costa Rica? Were they conceived and developed for environmental conditions, loading scenarios, soil types, and materials similar to those found in our country? Clearly, the answer is NO.